Numerical simulation of the fire emergency evacuation for a metro platform accident. (January 2021) - Xie, Jiabin; Chen, Kecheng; Kwan, Trevor Hocksun; Yao, Qinghe
A coupled analysis of agent behavior and Computational Fluid Dynamics (CFD) model is applied to investigate the fire evacuation effectiveness in a popular metro station in Guangzhou, China. Due to the high density and complexity of traffic, the concept of Required Safe Escape Time and Available Safe Escape Time (RSET/ASET), which is more flexible and adaptable than the "6 minutes" principle, is applied in the safety assessment of fire evacuation. To pursue a stable simulation of the coupled model, the standard Critical Radiant Flux is used to deter the tenability criteria for exposure to fire and heat. Various related factors, including the fire location, the Heat Release Rate (HRR) of fire, the crowd density, and the operation mode of escalators, are analyzed through a series of simulations. Results indicate that the interaction between fire and humans should not be neglected in the evacuation simulation. Both the fire location and the crowd density have a significant effect on the evacuation, while the HRR of fire has a minor impact. When the accident happens at the entrance of an escalator, RSET is 58.3% longer than that when the accident occurs in the middle of the platform. RSET grows with the increase of the crowd density linearly. Besides, the evacuation efficiency could be partly improved by changing escalators that usually operate in the descending mode into ascending mode.